PERENCANAAN PERKUATAN LERENG MENGGUNAKAN SHEET PILE PADA AREA TERMINAL JEMBATAN KACA KAB.PROBOLINGGO - Dwi Septy Wahyuningdiah; Laily Endah Fatmawati; Herry Widhiarto (Jurnal Teknik Sipil, 2023)
Soil is an important aspect in construction design, therefore soil bearing capacity is an aspect that determines the stability, feasibility and longevity of a structure. Some methods of soil handling include designing a retaining wall so that it can minimize the impacts that arise, especially in residential areas with different soil heights from one point to another. Slope stability analysis has a very valuable position in the design of civil construction structures. Several ways that can be used to avoid the formation of a collapse is with a retaining wall. The use of retaining walls used in the plan is cantilever walls and in this study the retaining walls to be used are sheet pile walls. In this study it was intended to plan slope reinforcement using sheet piles with the help of the plaxis program and to use the manual calculation of the fellenius method to determine the safety factor for slope stability to overcome landslide disasters on glass bridges. The purpose of using the Fellenius method is to calculate the safety factor of the slope, while the plaxis software is a finite component program for geotechnical applications where soil models are applied to simulate soil behavior.